The Impact of the Arab Narrative Heritageon Al- Zahawi's Long Poem ( An Upheaval at Hellfire) - Shareef, Fadhil Abdulameer (Al-Adab Journal, 2020)
The scientific literary religious and historical heritage is considered of high importance in the Arab modern and contemporary literature ,and history ,in general , is an rich resource of the poetic inspiration through which the poet can reflect the egression of era soul and rebuilding of the past according to a modern human vision that reveal the individual's concerns sufferings ambitions and dreams .This means that the past time keeps living with the present time and has a direct relationship controversial that depends on influence and affectivity .Hence, the modern writers have endeavored to reduplicate the heritage in details for the sake of heritage's revival in just in people' minds but also in writers' poetic products .In this sense, the innovative experience of Al-Zahawi poet and his strong link with the human heritage , investing this experience in expressing the Arab contemporary reality in his epic poem ( An Upheaval at Hellfire) which reflects his efficacy in Al-Maa'rri's Resaalat Al-Ghofran in addition to other heritage resources .In hisepic poem , Al-Zahawi had presented his philosophy , opinions , his way in life , and people and their beliefs through his record in hellfire as well as his efficacy in the Holly Quraan , the Prophet Hadith , origins of Arabic , western and Persian philosophies in addition to modern scientific iscoveries.